The role of financial system indicators in supporting economic development in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to shed light on the concept of the financial system, and study the impact of changing the indicators of the financial system that it needs to be one of the effective economic development tools, especially in the reconstruction phase, by shedding light on the fields of increasing or decreasing the percentage of its contribution to supporting the gross domestic product.The research depends on the descriptive analytical approach, and we used the multiple regression model, after the descriptive study of the study's indicators and the theoretical clarification of the concept of the financial system and its indicators.Among the most important results: There is a statistically significant effect of the indicators of the financial system on the GDP, which is expressed with an explanatory power of 79.3%, and the model shows that there is a positive and statistically significant effect of the volume of bank credit in the GDP, and a negative and statistically significant effect of the volume of government spending in Gross domestic product, while there is no statistically significant effect for the third independent variable (investment) in Gross domestic product.